2021
DOI: 10.14740/jocmr4524
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Intake by Meal Time Zone in Geriatric Patients Is Related to Nutritional Assessment Index

Abstract: Background:The blood metabolome profiles depend on the meal intake time zone regardless of having the same meal. The serum albumin (Alb) level, which is important in managing geriatric patients with chronic diseases, is included in the metabolome analysis. In this study, we aimed to examine the relationship between Alb and the nutritional value of hospital meals consumed at breakfast, lunch, and dinner among geriatric patients. Chrononutrition was considered while drawing inferences. Methods:We retrospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Breakfast NPC/N tended to be higher in the upper group than in the lower group. NPC/N indicates the ratio of non-protein energy intake (energy from carbohydrates and lipids) per gram of nitrogen contained in protein [ 6 ]. Therefore, higher amounts of energy were derived from carbohydrates and lipids in the upper Alb-RC group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Breakfast NPC/N tended to be higher in the upper group than in the lower group. NPC/N indicates the ratio of non-protein energy intake (energy from carbohydrates and lipids) per gram of nitrogen contained in protein [ 6 ]. Therefore, higher amounts of energy were derived from carbohydrates and lipids in the upper Alb-RC group.…”
Section: Discussionmentioning
confidence: 99%
“…NPC/N is an index that determines whether administered amino acids are effectively synthesized into proteins [ 6 ]. It is also an index applicable to hospital food ingested orally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NPC/N ratio indicates the amount of carbohydrates and protein that should be consumed per protein intake to maximize protein utilization [ 3 ]. In previous studies, we have shown that differences in nutrient intake from breakfast/lunch/dinner, which is calculated from nutritional intake obtained through hospital meals consumed by elderly patients might affect albumin (Alb) synthesis in the liver [ 4 ]. We also found that the NPC/N ratio in elderly patients’ nutritional intake may influence their discharge locations [ 5 ].…”
Section: Introductionmentioning
confidence: 99%